Diversity of Freshwater Fish in Fragmented Forest of Wilmar Oil Palm Plantation, Miri, Sarawak - Khairul Adha, A.Rahim; Melissa Dennis, Chong; Ahmad Syafiq, Ahmad Nasir; Fatimah A'tirah, Binti Mohamad; Farah Akmal, Idrus; Mohd Azlan Jayasilan, Abdul Gulam Azad; Awangku Shahrir, Naqiuddin (2021)
The study was conducted in the river system located at Wilmar oil palm plantation in Miri, Sarawak. The objective of the study is to determine the fish species diversity and composition in the streams and rivers in the oil palm plantations. Fish were sampled using a variety of fishing methods, including, scoop nets, cast net, and gill nets of different mesh sizes (1.0, 1.5, 2.0, 2.5, 3.75 and 4.0 cm) from 2 to 7 of February 2014. A total of 326 individual fish including 32 species of native fishes and one species of non-native fish from 19 genera, seven families and five orders were collected from seven locations. The cyprinid fish represented 62.20% of the total fish caught and was found in all the rivers surveyed. About six endemic species in Borneo such as Barbonymus collingwoodii, Barbodes banksi, Barbodes sealei, Hampala bimaculata Nematabramis borneensis and Nematabramis everetti were identified. However, only one species from families Bagridae, Balitoridae, Clariidae, and Hemiramphidae was sampled from the study sites. The higher fish species composition found in streams and rivers of the oil palm plantation landscapes could be attributed to the conservation of some areas of the plantation as high conservation value forest (HCVF) status, which have provided suitable habitat for fish species within the plantation aquatic environments.